TELEMEDICINE AS A DETERMINANT OF SUSTAINABLE REGIONAL ECONOMIC DEVELOPMENT: SOCIOECONOMIC MECHANISMS AND INSTITUTIONAL CONDITIONS - Lipych, L. H.; Liutak, O. M.; Kovalska, L.L. (Global Prosperity, 2026)
Telemedicine is regarded as a socioeconomic intervention that can modify spatial access to healthcare, household transaction costs, labour time losses, and regional health system resilience. Its relevance is evident in rural, peripheral, and war-affected territories, where transport barriers, staff shortages, infrastructure constraints, and unequal digital connectivity intensify disparities. Telemedicine should be analyzed as both a healthcare delivery technology and an intersectoral instrument for reducing spatial inequality, preserving human capital, and strengthening regional resilience. Objectives. The objectives are to conceptualize telemedicine as a factor of sustainable regional economic development and to identify mechanisms through which it affects spatial equity, household costs, productive time, human capital, and health system resilience. Materials and methods. The study applies a qualitative conceptual design based on a narrative review and synthesis of publications, reviews, policy documents, and Ukrainian regulatory sources. The framework covers household and time-related costs, productivity, resource allocation, spatial equity, human capital, digital infrastructure, and institutional conditions. Results. The study identifies six channels through which telemedicine may affect regional economic development: reducing travel-related and transaction costs, preserving productive time, improving productivity, optimizing resource allocation, mitigating spatial inequality in care access, and strengthening local system resilience. These effects depend on broadband connectivity, stable financing, institutional integration, and workforce digital readiness. Conclusions. Telemedicine should be interpreted as a conditional determinant of sustainable regional economic development, not an autonomous driver of regional growth. Its contribution is realized through mechanisms linking healthcare access, digital infrastructure, human capital, and territorial resilience.